1999
DOI: 10.1034/j.1399-3003.1999.13b06.x
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory and inspiratory chest computed tomography and pulmonary function tests in cigarette smokers

Abstract: This study evaluated small airway dysfunction and emphysematous destruction of lung parenchyma in cigarette smokers, using chest expiratory highresolution computed tomography (HRCT) and pulmonary function tests (PFT).The degree of emphysematous destruction was classified by visual scoring (VS) and the average HRCT number at full expiration/full inspiration (E/I ratio) calculated in 63 male smokers and 10 male nonsmokers (group A). The Brinkman smoking index (BI), defined as cigarettes . day -1 6 yrs, was estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 26 publications
1
39
1
Order By: Relevance
“…PI was defined as the proportion of pixels under −900 HU at expiration [20][21][22]. ATR was defined as the ratio of MVLA at expiration/inspiration [23,24]. RVC 860-950 was defined as follows:…”
Section: Image Data Reconstruction and Data Analysismentioning
confidence: 99%
“…PI was defined as the proportion of pixels under −900 HU at expiration [20][21][22]. ATR was defined as the ratio of MVLA at expiration/inspiration [23,24]. RVC 860-950 was defined as follows:…”
Section: Image Data Reconstruction and Data Analysismentioning
confidence: 99%
“…SPD was defined as 60% vital capacity or 50% forced expiratory volume in 1 s [11] . BI was obtained using the following equation: number of cigarettes smoked per day * number of years smoked [19] . The POSSUM scoring system is used to calculate the predictive mortality rate (R) using the following formula:…”
Section: Risk Factors For Postoperative Complicationsmentioning
confidence: 99%
“…The I/E lung volumes calculated from the chest CT view have been shown to correlate with pulmonary function (TLC and RV) [23][24][25]. Yamashiro and coworkers [20] have also demonstrated that E/I ratio in the chest CT significantly correlated with the following: the %FEV1 predicted (correlation coefficient, r = −0.56), FEV1/FVC (r = −0.59), and RV/TLC (r = 0.57), respectively.…”
Section: Discussionmentioning
confidence: 99%